2015
DOI: 10.2113/jeeg20.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies and Verification of the Vertical Array-Differential Target Antenna Coupling (DTAC) Method for Rapid Sensing and Imaging of Subsurface Targets

Abstract: We have developed a new electromagnetic geophysical system that has significantly improved target sensing and imaging capabilities compared to conventional measurements. In a previous series of papers, we described a new measurement technology called the Differential Target Antenna Coupling (DTAC) method, which used a magnetic-field transmitter (TX) and a magneticfield receiver (RX), oriented in a horizontal array, with separation distances of the order of tens of meters, and up to tens of kilometers. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To investigate the feasibility of such a system, Sternberg et al (2015a) studied the extension of the DTAC method to a moving, vertical TX/RX array, using a very low-power system over known tuned-coil targets. This null-field array utilizes a horizontal TX loop and an approximately orthogonal (nulled) two-axis RX that is located directly below the TX.…”
Section: Horizontal-array Dtac Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the feasibility of such a system, Sternberg et al (2015a) studied the extension of the DTAC method to a moving, vertical TX/RX array, using a very low-power system over known tuned-coil targets. This null-field array utilizes a horizontal TX loop and an approximately orthogonal (nulled) two-axis RX that is located directly below the TX.…”
Section: Horizontal-array Dtac Methodsmentioning
confidence: 99%
“…Sternberg et al (2015a) demonstrated some of the capabilities of the vertical-array DTAC method using very small-scale surveys and using artificial tuned-target coils. In this paper, we will expand the field testing of the DTAC method to more realistic targets.…”
Section: Objective Of This Papermentioning
confidence: 99%
“…In Sternberg et al (2015), we show experimental studies and verification for the vertical array-DTAC method. For these studies, we used small-scale subsurface targets to simulate commercial targets of interest, such as mineral, energy and water resources.…”
Section: Background On the Vertical Array-dtac Methodsmentioning
confidence: 99%
“…The rapidly moving measuring system requires the use of two receiver coils, which simultaneously measure the x and y fields, rather than the sequential measurement of the three field components that was used in the horizontal array-DTAC system Dvorak and Sternberg, 2013). The use of two separate receivers can be accomplished by using the simultaneous calibration procedure that is described in Sternberg et al (2015) and Sternberg and Dvorak (2002).…”
Section: Objectives In This Papermentioning
confidence: 99%
See 1 more Smart Citation